Graphite Furnace Atomic Absorption Spectrometrlc determination of blood lead with palladium modification - Granadillo, Victor; Navarro, Janeth; Romero, Romer (Investigación Clínica, 2013)
In this work we present a graphite furnace atomic absorption speetrometric method for blood lead using palladium as a chemical modifter. Whole blood was diluted 10-fold with a 0.1% v/v triton X-lOO solution; 10 ÂµL of this solution and 10 ÂµL of the palladium-based modifier (2 mg Pd/L. 2% w/v citric acid and 0.01 M nitric acid were injected onto the LÂ´vov platform by using the alternate volume mode. The following furnace operating parameters were used: (a) drying steps, 120 °C for 10s and 250 °C for 30s; (b) pyrolysis steps, 800 °C for 45s (with oxygen) and 1100 °C for 25s; (e) atomization, 1600 °C for 3s; (d) clean out, 2700 °C for 4s. Accuracy was tested by using (i) a NlST standard (SRM-909) and the Behring Control Blood for Metal 1 (OSSD 21) with lead coneentrations of 23.7 Ó 2.1 Âµg/L (found: 21.2 Ó0.7 Âµg/L) and 413 Ó51 Âµg/L (found: 407 Ó 6 Âµg/L), respectively: (ii) recovery studies (ca. 100 Ó 1 %), and (iii) a reported method (mean relative error: 5.1 %). Approximate standard deviations of 0.3 (within-run) and 0.7 (between-runs) Âµg Pb/L were found in the precision study. The detection limit (30) and the characteristic mass (for a 10- ÂµL injection volume) were 0.1 Âµg Pb/L Pb/L and 15 pg/0.0044 A s, respectively. The proposed method was used to establish the lead levels of patients with renal insufficiency; a mean concentration (Ó SO) of 59 Ó 39 Âµg Pb/L (range: 12 -160 Âµg Pb/L) was found. The method was interference-free, reliable and reproducible.